From incidents to remote work. Pre-pandemic experiences of working from home during the lockdown - Binder, Piotr (Research on social problems in (pre-)pandemic reality, 2023)
The paper attempts to analyze one of the aspects of social change, which is the progressive process of making work more flexible. The starting point was the thesis assuming that remote work's technical and organizational components and the practice of performing some professional duties remotely were popularized long before the pandemic. However, it was not indicated by the pre-pandemic measurements of forms of employment such as teleworking. The empirical basis of the text was 49 semi-structured qualitative interviews with people working remotely at the beginning of the pandemic. The presented analyzes were inspired, on the one hand, by the concept of teleworkability, which makes it possible to go beyond the binary stationary-remote opposition, and on the other, by the boundary theory, which sensitizes to changes taking place at the intersection of professional and private spheres. The analysis results are grounded in data typology of pre-pandemic experiences of remote work. Its interpretations indicate that remote work components gradually penetrated employees' lives, resulting in more flexible spatial and temporal frameworks while violating the boundaries between work and private life. These processes were also a source of valuable experience for employees forced to work remotely at the beginning of the pandemic. The spectrum of professional contexts in which these changes have been observed indicates a broader cultural background of transformations in the work sphere.